Propuesta de la documentación para el SG-SST con base en los estándares mínimos de la Resolución 0312 del año 2019 para la empresa Inversiones Punto Cinco S.A.S. (2021)
The following work consisted of preparing the design of the documentation for the SGSST por Inversiones Punto Cinco S.A.S. company, following the requirements defined in the minimum standards established by Resolution 0312 of the year 2019, the above in order to help the company to comply with these legal requirements. The documentation was designed following the PHVA cycle and to carry it out, it was necessary to start with a self-assessment of the current situation of the company in relation to compliance with the 30 minimum standards that a company of the magnitude and risk such as the de Inversiones Punto Cinco SAS, followed by this first activity, the risk identification matrix was documented and valued, as a third activity the documentation was prepared as identified in the initial diagnosis, this documentation includes sociodemographic studies, design of the job profile , documented procedures for the copasst and emergency brigades, prevention plan and emergency preparedness, procedures and various records for the good performance of the SG-SST in the company. Finally, a cost-benefit study is carried out, where it indicates the benefits of doing all the documentation and recommendations are given to Inversiones Punto Cinco S.A.S. company.